Thalamic volume differentiates multiple sclerosis from neuromyelitis optica spectrum disorder: MRI-based retrospective study - Manal Alosaimi; Hatham Alkanhal; Saleh Aldeligan; Nuha Alkhawajah; Alaa Albishi; Bander Hilabi; Salman Aljarallah (Frontiers in Neurology)
Multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOSD) are distinct demyelinating diseases of the central nervous system, each characterized by unique patterns of motor, sensory, and visual dysfunction. While MS typically affects the brain and spinal cord, NMOSD predominantly targets the optic nerves and spinal cord. This study aims to elucidate the morphometric differences between MS and NMOSD by focusing on gray matter volume changes in specific brain regions. We also examined if temporal changes in follow-up MRI differentiate the two disorders. We analyzed anatomical T1-weighted MRI scans from 24 patients with NMOSD and 25 patients with MS using the CAT12 toolbox. Our analysis revealed significant differences in gray matter structure between the two patient groups. Notably, the thalamus was found to be consistently smaller in patients with MS compared to those with NMOSD. This finding aligns with previous research highlighting thalamic atrophy as a hallmark of MS and further underscores the thalamus’s role in the disease’s pathology. These results provide valuable insights into the distinct neuroanatomical features of MS and NMOSD, contributing to a better understanding of the mechanisms underlying these diseases. The study also emphasizes the importance of advanced imaging techniques in differentiating between MS and NMOSD, which may have implications for diagnosis and treatment strategies.